Synthesis of Zr2Al3C4 coatings on zirconium-alloy substrates with AlC/Si interlayers as diffusion barriers. (February 2019) - Liang, Jiamin; Wei, Qiang; Ge, Fangfang; Ren, Donglou; Wang, Ji; Dong, Yue; Eklund, Per; Huang, Feng; Du, Shiyu; Huang, Qing
Abstract: Zr2 Al3 C4 coatings are potential candidates to prevent claddings of traditional Zr-based alloys from severe oxidation in water steam at high temperature. However, the diffusion of aluminum between coating and substrates at high temperature results in a coating composition deviating from the compositional domain for formation of the Zr2 Al3 C4 phase. Thus, synthesis of Zr2 Al3 C4 coatings on zirconium-alloy substrates is challenging. Here, we report that the Zr2 Al3 C4 phase can be obtained on zirconium alloy (ZIRLO) substrates where an AlC/Si interlayer deposited by magnetron sputtering is introduced. The AlC/Si interlayer prevented elemental diffusion of aluminum between the ZrAlC coating and the substrates during a post-annealing process at 800 °C for 3 h. The Al/Zr ratio of the ZrAlC coating after annealing was ∼0.96 and ∼0.59 in the cases of with and without AlC/Si interlayer, respectively. Hence, the AlC/Si interlayer acts as diffusion barrier and greatly decreases the deviation from the standard stoichiometric ratio of the Zr2 Al3 C4 phase, which facilitates the formation of the Zr2 Al3 C4 phase in the final coating. Highlights: The stoichiometry of Zr-Al-C in deposited coating change a lot during post annealing due to the Al diffusion into Zr substrate. The interlayer barrier is crucial to inhibit the inter-diffusion of elements between Zr substrate and Zr2 Al3 C4 coating. Zr2 Al3 C4 coatings are successfully synthesized on zirconium-alloy that will be one of promising candidates as accident tolerant fuel cladding.